2016
DOI: 10.1016/j.jml.2015.10.002
|View full text |Cite
|
Sign up to set email alerts
|

A predictive framework for evaluating models of semantic organization in free recall

Abstract: Research in free recall has demonstrated that semantic associations reliably influence the organization of search through episodic memory. However, the specific structure of these associations and the mechanisms by which they influence memory search remain unclear. We introduce a likelihood-based model-comparison technique, which embeds a model of semantic structure within the context maintenance and retrieval (CMR) model of human memory search. Within this framework, model variants are evaluated in terms of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 66 publications
(184 reference statements)
3
52
1
Order By: Relevance
“…In the current study, unlike in these prior studies, we identified subsequent serial recall effects, which involve strong temporal organization, that were limited to the vlPFC. While this may appear inconsistent with the previous studies, it is not clear that temporal and semantic organization would be mediated by the same mechanisms (Morton and Polyn, 2016). Furthermore, there is some evidence suggesting that the vlPFC in particular contributes to episodic recall.…”
Section: Discussioncontrasting
confidence: 97%
“…In the current study, unlike in these prior studies, we identified subsequent serial recall effects, which involve strong temporal organization, that were limited to the vlPFC. While this may appear inconsistent with the previous studies, it is not clear that temporal and semantic organization would be mediated by the same mechanisms (Morton and Polyn, 2016). Furthermore, there is some evidence suggesting that the vlPFC in particular contributes to episodic recall.…”
Section: Discussioncontrasting
confidence: 97%
“…In calculating semantic similarity for the analyses reported below, we used LSA. We note that almost identical results are obtained when the same analyses are conducted using Word Association Space (WAS; Steyvers et al, 2004) cos(θ) values which some evidence suggests better predicts subjects' transitions than LSA (Morton & Polyn, 2016).…”
Section: Quantifying the Temporal Contiguity And Semantic Contiguity supporting
confidence: 60%
“…[ 23,110] Distance Words with short semantic or associative distance are judged as more semantically related, remembered better in paired-associate learning tasks, retrieved closer to each other in free recall or verbal fluency tasks, produce stronger priming effects in naming tasks, and lead to faster sentence verification and recognition. [22,48,70,102,[111][112][113][114][115][116] [117,118] Words with low phonological or orthographic distance produce stronger priming effects.…”
Section: Centralitymentioning
confidence: 99%